'Survivorship' in prostate cancer I: diagnostic and management considerations. Issue 3 (23rd May 2013) - Kirby, Roger; Sharp, Owen; Forster, Paul
Abstract With more than 250 000 men currently surviving after a diagnosis of prostate cancer in the UK, doctors need to adopt a more patient‐focused approach to help improve their quality of life. Copyright © 2013 John Wiley & Sons